Pelatihan Bantuan Hidup Dasar (BHD) bagi Masyarakat di Wilayah Puskesmas Oesapa Kota Kupang - Serly Sani Mahoklory (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Abstract Out-of-hospital cardiac arrest is a life-threatening emergency that requires immediate intervention to prevent death and irreversible brain damage. Basic Life Support (BLS) plays a crucial role as an initial response that can be performed by laypersons before professional medical assistance arrives. However, the level of knowledge and skills related to BLS among community members remains limited, particularly in the working area of Puskesmas Oesapa.This community service program aimed to improve the knowledge and practical skills of the community in performing Basic Life Support. The methods applied included health education sessions, demonstrations, and hands-on practice using mannequins. Participants consisted of local residents, including health cadres and community members. The results showed a significant improvement in participants’ understanding of cardiac arrest recognition and the correct steps of BLS. In addition, participants demonstrated better skills and confidence in performing cardiopulmonary resuscitation (CPR) during simulations. In conclusion, the BLS training program effectively enhanced community preparedness in responding to emergency situations. Continuous and periodic training is recommended to sustain and further improve community competence in life-saving interventions. Keywords: Basic Life Support, Cardiopulmonary Resuscitation, Community Service, Emergency Response Abstrak Henti jantung mendadak merupakan salah satu penyebab kematian tertinggi yang dapat terjadi kapan saja dan di mana saja, termasuk di lingkungan masyarakat. Penanganan awal melalui Bantuan Hidup Dasar (BHD) sangat penting untuk meningkatkan peluang keselamatan korban sebelum mendapatkan pertolongan medis lanjutan. Namun, pengetahuan dan keterampilan masyarakat terkait BHD masih tergolong rendah. Kegiatan Pengabdian kepada Masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan masyarakat di wilayah Puskesmas Oesapa Kota Kupang dalam melakukan tindakan BHD secara tepat. Metode yang digunakan meliputi penyuluhan, demonstrasi, dan praktik langsung dengan media manekin. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta terkait langkah-langkah BHD, serta peningkatan keterampilan dalam melakukan resusitasi jantung paru (RJP). Dengan demikian, pelatihan ini efektif dalam meningkatkan kesiapsiagaan masyarakat dalam menghadapi kondisi kegawatdaruratan. Kata Kunci: Bantuan Hidup Dasar, Resusitasi Jantung Paru, Pengabdian Masyarakat, Kegawatdaruratan